A coordinated synthesis and conjugation strategy for the preparation of homogeneous glycoconjugate vaccine candidates. - Grayson, E; Bernardes, G; Chalker, J; Boutureira, O; Koeppe, JR; Davis, B (2011)
A sweet solution: A strategy for the synthesis of well-defined carbohydrate-based vaccines is presented. The approach couples complex oligosaccharide synthesis to site-specific conjugation methodology to provide pure glycoprotein vaccine candidates (see scheme). Copyright © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.